The role of hormones on Toxoplasma gondii infection: a systematic review - Galván-Ramírez, María de la Luz; Gutiérrez-Maldonado, Adrián Fernando; Verduzco-Grijalva, Fabiola; Jiménez, Judith Marcela Dueñas (Frontiers in Microbiology, 2014)
Background: Toxoplasma gondii is the causal agent of toxoplasmosis in which one third of the world’s population has been infected. In pregnant women, it may cause abortion and severe damage to the fetal central nervous system. During pregnancy, the prevalence of toxoplasmosis increases throughout the second and third quarter of gestation, simultaneously progesterone and 17β-estradiol also increase. Thus, it has been suggested that these hormones can aggravate or reduce parasite reproduction. The aim of this study was reviewing the relationship between hormones and infection caused by T. gondii in several experimental animal models and humans, focused mainly on: a) congenital transmission, b) parasite reproduction, c) strain virulence, d) levels of hormone in host induced by T. gondii infection and e) participation of hormone receptors in Toxoplasma gondii infection. Are the hormones specific modulators of T. gondii infection? A systematic review methodology was used to consult several databases (Pub Med, Lilacs, Medline, Science direct, Scielo, Ebsco, Sprinker, Wiley and Google Scholar) dated from September, 2013 to March, 2014. Results: 30 studies were included; eight studies in humans and 22 in animals and cell cultures. In the human studies, the most studied hormones were testosterone, progesterone, prolactin and 17-ß estradiol. Type I (RH and BK) and Type II (Prugniaud, SC, ME49,T45, P78 and T38) were the most frequent experimental strains. Conclusions: Thirty-five years have passed since the first studies regarding Toxoplasma gondii infection and its relationship with hormones. This systematic review suggests that hormones modulate Toxoplasma gondii infection in different animal models. However, given that data were not comparable, further studies are required to determine the mechanism of hormone action in the Toxoplasma gondii infectious process.